An exploratory study on teaching and learning speaking English at Binh Gia high school - Lang Son: Problems and solutions - Lương, Thị Huyền (ĐHNN, 2017)
This minor thesis aimed at investigating some difficulties that students and teachers at Binh Gia High School have encountered in learning and teaching English speaking skill and suggesting solutions to overcome these difficulties. The subjects of the study were 120 students and 12 teachers of English.